Síntese e caracterização de nanocompósitos e de híbridos de polímeros conjugados/nanomateriais de carbono para aplicação em supercapacitores - Ana Paula Pereira Alves (2017)
In this work, we synthesized hybrids based on poly(3-hexylthiophene) (P3HT)/ multi- walled carbon nanotubes (MWCNT) and ternary nanocomposite composed of polypyrrole (PPy), reduced graphene oxide (RGO) and zirconium oxide. In both cases, the materials were characterized to better understand the relation between structure and property, and the fabricated materials were evaluated as the active materials in supercapacitors devices. The main goal is to contribute to the storage and energy conversion area associated to electronic equipment and the use of renewable energy. First, two types of P3HT and MWCNT hybrids there were prepared, one covalently linked between the components was synthesized by in-situ oxidative polymerization of 3- hexylthiophene (3HT) in the presence of MWCNT previously functionalized with a monomeric unit of thiophene. The second one was prepared by the polymerization of 3HT in the presence of MWCNT functionalized with amine groups, forming a non-covalent hybrid (P3HT/MWCNT). The hybrids were synthesized with a 1:1 (polymer:MWCNTs) mass ratio. -1 -1 The covalent hybrid (P3HTMWCNT) achieved an electrical conductivity of 4.6×10 S cm , which was 5 times higher than that of the other hybrid. The chemical structure, morphology and electrochemical properties of the hybrids were compared with those of neat P3HT and neat MWCNTs. Thus, the covalent hybrid which showed superior connection between the two components and it was easily dispersed in common organic solvents, was chosen for the study of supercapacitors. This material showed a high performance reaching a specific -1 -1 capacitance of 312 F g at a scan rate of 10 mV s , which was seven times higher than the supercapacitor based on MWCNT. In the second part, we were synthesized ternary composites composed of PPy/RGO/ZrO2, using a simple and easily scalable one-step chronopotenciometry method. This work was developed at Rice University (Houston, TX, USA) (visiting scholar program- CNPq) with the collaboration of the group of Prof. P. Ajayan. The detailed characterization revealed that the addition of rGO and ZrO2 modified the morphology and the structure of the electrode material compared with those based on binary composite PPy/rGO and pure PPy. -1 -1 The 3D architecture reached a specific capacitance value of 341 F g at 5 mV s , which was 1.6 and 2 times higher than the unary and binary, respectively. The ternary composite featured high stability, with an increase of 5% in capacitance after a thousand cycles. The devices based on different compositions of conjugated polymers (PC) and carbon nanomaterials developed in this work presented good results of electrochemical properties, and long-term stability and can be candidates for the preparation of flexible devices with technological potential.